FORECASTING COSMETIC INVENTORY ON MS GLOW MABELLA STORE RANGE WITH WMA METHOD - Vira Fahrani; William Ramdhan; Wan Mariatul Kifti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
MS Glow Mabella Store Kisaran is a business that is engaged in selling cosmetic products such as make-up cosmetics and cosmetic care which is located on Jalan Imam Bonjol Kisaran. Makeup cosmetics are materials used to make up yourself with the aim of making it look more attractive or what is often referred to as Make-up. While cosmetic treatments are ingredients that are used on the human body to keep the body healthy and beautiful or often referred to as skincare. According to the results of interviews and observations of MS Glow Mabella Store Kisaran. Demand for cosmetic products by customers tends to change according to the trends that occur. In general, the use of cosmetics is used by women. This concerns the interests of many people, especially women in terms of awareness of using make-up and skincare in order to beautify themselves and make the body look healthy and well-groomed. This has a major impact on the demand for cosmetic supplies owned by MS Glow Mabella Store Kisaran. Determination of cosmetic inventory is unpredictable, so it is not in accordance with the number of customer requests and often experiences a lack of inventory conditions contained in the MS Glow Mabella Store Kisaran